Alternative approaches to practical work in a biology classroom – meeting the needs of our students - Astuti, Elisabeth Endah Kusuma; Sriyansyah, Syakti Perdana; Barrera, Jeffrey DC (Education and Development Research, 2024)
Most science teachers regard practical work as an essential requirement for science teaching. There is, however, research-based evidence suggesting that how practical work might best be assessed and carried out in high school science was still ineffective and controversial. Here, the conceptual and procedural knowledge of 110 secondary students as they carried out the practical work in science courses are explored. Regardless of the amount and details of prior instruction that the students get, the descriptive analysis method was used to investigate the extent to which students at the secondary level can both explain biological concepts and perform practical procedures after participating in practical work. A total of 30 open-ended questions were given to students after completing four practical works on the topics of cells, food testing, photosynthesis, and urine testing. Students performed slightly better in procedural knowledge (65) compared to conceptual knowledge (64), with both scores out of 100. The results thus far are consistent with findings from previous studies, which indicate that practical work lacks emphasis on the minds-on aspects. It also shows that procedural knowledge, which is not currently, summatively assessed in Indonesian school science, has not been fully mastered by students even after carrying out practical work. To address this issue, the alternative to a practical test as an indirect assessment of practical skills (IAPS) from England has been adapted to the assessment of practical work in an Indonesian classroom setting. The considerations and limitations are discussed.